Influence of the induced membrane filled with syngeneic bone and regenerative cells on bone healing in a critical size defect model of the rat's femur. Issue 10 (October 2018) - Nau, Christoph; Simon, Sebastian; Schaible, Alexander; Seebach, Caroline; Schröder, Katrin; Marzi, Ingo; Henrich, Dirk
Abstract: Introduction: The induced membrane technique for the treatment of large bone defects consists of a 2-stage procedure. In the first stage, a polymethylmethacrylate (PMMA) cement spacer is inserted into the bony defect of a rat's femur and over a period of 2–4 weeks a membrane forms that encapsulates the defect/spacer. In a second operation the membrane is opened, the PMMA spacer is removed and the resulting cavity is filled with autologous bone. Since little effort has been made to replace the need for autologous bone this study was performed to elucidate the influence of different stem cells and the membrane itself on bone healing in a critical size femur defect model in rats. Especially the question should be addressed whether the use of stem cells seeded on a β-TCP scaffold is equivalent to syngeneic bone as defect filling in combination with the induced membrane technique. Materials and Methods: A total of 96 male Sprague-Dawley (SD) rats received a 10 mm critical size defect of the femur, which was stabilized by a plate osteosynthesis and filled with PMMA cement. In a second step the spacer was extracted and the defects were filled with syngeneic bone, β-TCP with MSC + EPC or BM-MNC. In order to elucidate the influence of the induced membrane on bone defect healing the induced membrane was removed in half of the operated femurs. The defect area was analysed 8 weeks later for bone formation (osteocalcin staining), bone mineral density (BMD) and bone strength (3-point bending test). Results: New bone formation, bone mineral density and bone stiffness increased significantly, if the membrane was kept. The transplantation of biologically active material (syngeneic bone, stem cells on b-TCP) into the bone defect mostly led to a further increase of bone healing. Syngeneic bone had the greatest impact on bone healing however defects treated with stem cells were oftentimes comparable. Conclusion: For the first time we demonstrated the effect of the induced membrane itself and different stem cells on critical size defect healing. This could be a promising approach to reduce the need for autologous bone transplantation with its' limited availability and donor site morbidity.